Timing of auditor terminations and client firm risk. Issue 6 (31st May 2019) - Her, Young-Won; Howard, Jennifer; Son, Myungsoo
Abstract : Purpose: The purpose of this study is to examine whether the timing of auditor terminations signals the riskiness of client firms. Design/methodology/approach: This empirical study uses a sample of auditor switches during 2003-2014 to conduct univariate tests and multivariate regression analyses. Auditor switches occurring after the audit report date but before the shareholders' meeting are classified as "planned" terminations and auditor switches that occur outside of this window are classified as "abrupt" terminations. Findings: First, abrupt terminations are more strongly related to client risk factors than planned terminations. Second, relative to planned terminations, abrupt terminations are more likely to result from an auditor resignation rather than a client dismissal. Third, abrupt termination firms are more likely to have internal control weaknesses and experience delistings in the following year. Future operating performance is also worse after an abrupt termination. Finally, auditors and investors view abrupt terminations as riskier than planned terminations. Practical implications: As the timing of the auditor termination is publicly available information, it can provide an important signal of deteriorating financial performance to shareholders and potential investors. Abrupt terminations could be costly to shareholders because those firms likely have lower quality financial reporting (due to internal control weakness) and deterioration of future operating performance. Originality/value: While concurrent studies investigate the relation between the timing of new auditor appointment and audit quality, this is the first study to document the relation between the timing of auditor termination and the riskiness of client firms.